A new role for P2X4 receptors as modulators of lung surfactant secretion - Miklavc, Pika; Thompson, Kristin E.; Frick, Manfred (Frontiers in Cellular Neuroscience, 2013)
In recent years, P2X receptors have attracted increasing attention as regulators of exocytosis and cellular secretion. In various cell types, P2X receptors have been found to stimulate vesicle exocytosis directly via Ca2+ influx and elevation of the intracellular Ca2+ concentration. Recently, a new role for P2X4 receptors as regulators of secretion emerged. Exocytosis of lamellar bodies (LBs), large storage organelles for lung surfactant, results in a local, fusion-activated Ca2+ entry (FACE) in alveolar type II epithelial cells. FACE is mediated via P2X4 receptors that are located on the limiting membrane of LBs and inserted into the plasma membrane upon exocytosis of LBs. The localized Ca2+ influx at the site of vesicle fusion promotes fusion pore expansion and facilitates surfactant release. In addition, this inward-rectifying cation current across P2X4 receptors mediates fluid resorption from lung alveoli. It is hypothesized that the concomitant reduction in the alveolar lining fluid facilitates insertion of surfactant into the air–liquid interphase thereby “activating” it. These findings constitute a novel role for P2X4 receptors in regulating vesicle content secretion as modulators of the secretory output during the exocytic post-fusion phase.